Digitalization of Payments through E-Money and Monetary Dynamics as Determinants of Inflation in Indonesia: ECM Analysis for the Period 2015–2024 - Jenny Alfianti; Nur Ina Avia; Wildia Nusayfi; Ikmalul Rizal (Penerbit Hellow Pustaka, 2026)
From 2019 to 2024, the use of electronic money increased rapidly in Indonesia in line with the acceleration of digitalization during the pandemic and the economic recovery period. These changes affected the money supply, potentially driving inflation. Furthermore, exchange rate fluctuations and interest rate adjustments during this period became a primary concern for the government in maintaining economic stability. This study analyzes the influence of e-money, the exchange rate, and interest rates on inflation in Indonesia using the Error Correction Model (ECM) approach. The results show that all independent variables significantly influence inflation. A high R value indicates a good fit for the model. The ECT coefficient is significant and negative, indicating that adjustment to long-run equilibrium occurs within approximately one year. This finding confirms that monetary policy must consider the effects of time lag and the dynamics of digital transactions in an effort to maintain macroeconomic stability.